Seismically Induced Snow Avalanches: The Central Italy Case - Piacentini, Tommaso; Calista, Monia; Crescenti, Uberto; Miccadei, Enrico; Sciarra, Nicola (Frontiers in Earth Science, 2020)
Snow avalanches are critical events due to the sudden instability of snow in mountain regions. Seismically induced snow avalanches, due to a particular type of trigger perturbing snow-covered slopes, are occasional events in geodynamically active mountain regions around the world, which can lead to large anomalous avalanches. The seismic trigger of an avalanche is either simultaneous or delayed. In Italy, the Alps, and particularly the Apennines, feature large areas expected to be affected by seismically induced snow avalanches. In this work, the avalanches’ distribution in Central Italy (i.e., Abruzzo region) and its connection with moderate–high seismicity were investigated. With regional and historical analyses, we investigated the connection between avalanches and seismicity. We revealed two main events of seismically induced avalanches (6–9 April 2009, western Gran Sasso-Assergi area, and 18 January 2017, Gran Sasso massif) characterized by an anomalous distribution of avalanches. A specific and detailed analysis focused on the northeast Mt. Siella slope, where well-documented and constrained events occurred on 18 January 2017 in the Gran Sasso area, affecting a tourist facility. This involves geomorphological and photogeological multitemporal investigations. Moreover, the Rigopiano avalanche was analyzed through 3D numerical modelling and stability analysis of the snow to investigate the possible seismic trigger. We found the avalanche was consistent with delayed seismically induced avalanche cases. This combination contributed to a more general assessment of the seismically induced avalanches in the Central Apennines area (i.e., Abruzzo region) and provided new examples of seismically induced avalanches at both the regional and detailed scales, which are largely consistent with the world distribution.